Pengaruh Suku Bunga dan Jumlah Uang Beredar (M1) Terhadap Inflasi di Sumatera Utara: Peran Bank Sentral Sebagai Otoritas Moneter - Oktania, Ainur; Alisya, Jeane; Nainggolan, Noubel Putra; Putri, Dwi Nabila; Manihuruk, Frido Evindey (STIE Jambatan Bulan, 2024)
This study analyzes the effect of interest rates (BI rate) and money supply (M1) on inflation in North Sumatra Province by looking at the role of Bank Indonesia as the monetary authority. Quantitative methodology with multiple regression analysis is used in data processing in this study and uses annual data (2005-2020) obtained from the Central Bureau of Statistics of North Sumatra, Bank Indonesia and the Indonesian national website which is also a source of analysis. The results show a positive and significant impact of interest rates on inflation, while money supply (M1) has a positive but insignificant impact. With a coefficient of determination of 67.36%, most of the variation in inflation is explained by interest rates (BI rate) and money supply (M1). The results have important implications for economic policy formulation and effective decision making in maintaining price stability at the regional level by Bank Indonesia